PERKEMBANGAN DEMOKRASI DI NEGARA INDONESIA - Benny Bambang Irawan (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2007)
Democracy born due to equality before the law and protection of human right, starting from American Declaration 1776 and France 1789. The Democracy development concept conforms with the changing of constitution in force conceptually, each constitution forms understanding and ordering democracy follows the vision of constitution maker. Historisly, the application of democracy concept has many changed. The state convention has changed democracy concept contraction many times. The state has dominant rule for democracy execution by state executor. The configuration of politic with basic thinking toward the democracy changing in concept and execution.